Pelatihan dan Pengembangan Projek Penguatan Profil Pelajar Pancasila (P5) pada Kurikulum Merdeka di SD Negeri Unggulan 11 Pulau Morotai - Irawati Sabban; Risky Richlos Sarapung; Nurhani Mahmud (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
The P5 training at SD Negeri Unggulan 11 Pulau Morotai aims to enhance teachers' understanding and skills in implementing the Pancasila Student Profile (P5) as part of the Kurikulum Merdeka. This training is designed with consideration for the region's limited access and understanding, covering three main aspects: P5 concept socialization, project design, and the implementation of P5 projects in schools. The program is conducted in two stages, namely project planning and implementation, followed by evaluation using quantitative and qualitative methods. The training results showed a significant improvement in participants' knowledge, with the average pretest score of 36.5 rising to 83 in the posttest. The first P5 project implemented was themed "Build the Body and Soul," focusing on reforestation activities aimed at increasing students' environmental awareness. The evaluation revealed a better understanding of the P5 dimensions, including values of collaboration, independence, and critical thinking skills. Moreover, the training succeeded in strengthening collaboration among school stakeholders, such as the principal, teachers, and supervisors. With this training, it is expected that SD Negeri Unggulan 11 can independently develop and implement P5 projects that are relevant to local needs, sustainable, and improve the quality of education in the school.